Time pressure review in maintaining audit quality, in Covid-19 pandemic: Psychological perspective - Purwanto Wahyudi; Suhartono Suhartono; Andi Muhammad Agung; Andi Wawo (Universitas Hayam Wuruk Perbanas, 2022)
This study is a qualitative study with a phenomenological approach to improve or maintain the quality of audits during the covid-19 pandemic in terms of time pressure taking into account psychological perspective. The results of this study showed that public accounting firm S. Mannan, Ardiansyah and Partners experienced a change in audit work patterns that is before the pandemic was done only directly but in the midst of this pandemic is done by two methods, namely directly and indirectly (remotely). The current audit quality at public accounting firm S.Mannan Ardiansyah, have taken steps to do so and have also followed the instructions and technical directions of online management, then the audit process is also based on the direction of the Indonesian Institute of Public Accountants (IAPI). The time pressure faced by auditors in the midst of the current pandemic give an impact from auditor psychology, this is due to pressures that make auditors have to complete their work in an efficient time but during a pandemic there is evidence collection of audits done online it is vulnerable to errors in auditing.